다문화가족 자녀 어머니의 개인변인에 따른 가정환경 - 오성숙(Seong-Sook Oh); 이은경(Eun-Kyoung Lee) (한국콘텐츠학회 논문지, 13(11), 2013)
The purpose of this study was to investigate language receptive characteristics of children with multicultural families in according to living areas. The subjects were 132 mother with children for living multicultural families 3 to 6 years old. The results were as follows. First, the differences of home environment on nationality, all variables were significant differences on emotional atmosphere, experience's variety, and play data in statistically. Second, the differences of home environment on age all variables were significant differences on permission, independent's upbringing emotional atmosphere, experience's variety and physical environment in statistically. Third, the differences of home environment on educational background, all variables were significant differences on predictable environments, developmental stimulation, quality of language environments, permission, independent's upbringing emotional atmosphere, experience's variety, physical environment and play data in statistically. Fourth, the differences of home environment on communication method in home, all variables were significant differences in statistically as communication(general korean) they use in home. Fifth, the differences of home environment on occupation existence, all variables were not significant differences in statistically. 본 연구는 만 3세에서 6세 다문화가족 자녀 어머니의 개인변인에 따라 가정에서 자녀에게 제시하는 가정환경에 차이가 있는지를 알아보고자 하였다. 연구결과는 첫째, 국적에 따른 가정환경의 차이를 살펴보면 정서적 분위기, 경험의 다양성, 놀이 자료에서 통계적으로 유의한 차이가 있는 것으로 나타났다. 둘째, 연령에 따른 가정환경의 차이에서는 허용성, 독립성의 육성, 정서적 분위기, 경험의 다양성, 물리적 환경에서 통계적으로 유의한 차이가 있는 것으로 나타났다. 셋째, 학력에 따른 가정환경의 차이에서는 안정된 환경, 발달을 돕는 자극, 언어적 환경의 질, 독립성의 육성, 정서적 분위기, 경험의 다양성, 물리적 환경, 놀이 자료에서 통계적으로 유의한 차이가 있는 것으로 나타났다. 넷째, 가정 내 의사소통방법에 따른 가정환경의 차이에서는 모든 변인에서 통계적으로 유의한 차이가 있는 것으로 나타났다. 다섯째, 직업유무에 따른 가정환경의 차이에서는 모든 변인에서 통계적으로 유의한 차이가 없는 것으로 나타났다.